Grinding stone rod and grinding method

By controlling the average particle size of mullite crystals in the inorganic long fiber abrasive of the grinding stone rods to be less than 25 nm, the problem of insufficient surface roughness and wear resistance when grinding the mold is solved, and a more efficient grinding effect and a longer service life are achieved.

CN119630510APending Publication Date: 2025-03-14TAIMEI CHEM CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202380055053.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-02-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When grinding a mold, the existing grinding stone rods are difficult to achieve the desired surface roughness and are not sufficient to wear resistance.

Method used

Abrasives of inorganic long fibers are used, wherein the inorganic long fibers have 80 to 90% by weight of alumina components and 20 to 10% by weight of silica components. In the crystal structure, the average particle size of the mullite crystal is controlled to be less than 25 nm to suppress scratches and brittle rupture.

Benefits of technology

The surface roughness of the surface of the workpiece grinding object is improved, and the wear resistance of the grinding stone rod is improved, ensuring grinding force and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630510A_ABST
    Figure CN119630510A_ABST
Patent Text Reader

Abstract

The grinding stone rod (10) grinds a surface (S) to be ground of a workpiece (W) by pressing the front end part (17) on the surface (S) to be ground. The grindstone rod (10) has inorganic long fibers (15) and a cured resin impregnated in the inorganic long fibers (15). The inorganic long fibers (15) have 80-90% by weight of an alumina component and 20-10% by weight of a silica component. The crystal structure of the inorganic long fibers (15) comprises mullite crystals and intermediate alumina. The average particle size of the mullite crystals is less than 25nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a grinding stone rod and also to a grinding method using the grinding stone rod. Background Art

[0002] Patent document 1 describes a rod-shaped grinding stone made by impregnating a bundle of inorganic long fiber filaments with resin and curing the resin. The grinding stone in the same document is used for grinding molds. The grinding stone has a rectangular or circular cross section and has elasticity to bend in a direction intersecting with its axis. The inorganic long fiber filaments extend along the axis of the grinding stone, and the cross section of the filaments is exposed at the front end of the grinding stone.

[0003] In patent document 1, when grinding the grinding target surface of a workpiece, the base of the grindstone rod is held on a tool holder. In addition, the tool holder is connected to the main shaft of a machine tool, the main shaft is rotated, and the front end face of the grindstone rod is pressed against the grinding target surface of the workpiece. Here, the tool holder converts the rotation of the main shaft into a linear reciprocating motion and a rotational motion in the axial direction of the main shaft. Therefore, the front end of the grindstone rod is intermittently pressed against the workpiece to grind the grinding target surface. In addition, the front end of the grindstone rod contacts the workpiece in a rotating state to grind the grinding target surface.

[0004] Patent document 2 describes an abrasive for a grindstone. The abrasive in the same document is composed of inorganic long fibers impregnated with resin. The inorganic long fibers have 80 to 90 weight % of an aluminum oxide component and 20 to 10 weight % of a silicon dioxide component. The crystal structure of the inorganic long fibers has mullite crystals and intermediate aluminum oxide. The average particle size of the mullite crystals is 25 nm to 70 nm. In the abrasive in the same document, the inorganic long fibers contain more than 80 weight % of an aluminum oxide component, so the hardness of the inorganic long fibers is high. In addition, the average particle size of the mullite crystals is above 25 nm, so the grinding force for grinding and grinding the workpiece is large.

[0005] Patent Document 2 describes a rectangular parallelepiped grindstone made of the above-mentioned abrasive. When grinding a workpiece, the entire side surface of the grindstone extending in the long side direction is pressed against the grinding target surface of the workpiece. Furthermore, the grindstone is reciprocated along the grinding target surface.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6832555

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 10-183427 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] If the grinding stone abrasive material recorded in Patent Document 2 is formed into a rod shape to make a grinding stone rod, the grinding stone rod can have sufficient grinding force. However, with the precision of molds in recent years, the grinding stone rod composed of the grinding stone abrasive material recorded in Patent Document 2 sometimes cannot obtain the desired surface roughness by grinding. In addition, after the inventors devoted themselves to research, they found that the wear resistance of the grinding stone rod composed of the grinding stone abrasive material recorded in Patent Document 2 still has room for improvement.

[0012] The technical problem to be solved by the present invention is to provide a grindstone rod capable of improving the surface roughness and wear resistance of the grinding target surface of a workpiece in view of the above problem. In addition, the present invention also aims to provide a grinding method using such a grindstone rod.

[0013] Technical solutions adopted to solve technical problems

[0014] The inventors of the present invention have found, after intensive research, that when a grinding stone rod uses an abrasive in which inorganic long fibers have 80 to 90 weight % of an aluminum oxide component and 20 to 10 weight % of a silicon dioxide component and the crystal structure of the inorganic long fibers has an intermediate of aluminum oxide and mullite, the larger the grains of the mullite crystals in the crystal structure, the easier it is for scratches (grinding scars) to be generated on the grinding surface of the workpiece.

[0015] In addition, the inventors of the present invention have found that when the grinding stone rod uses an abrasive in which the inorganic long fiber has 80 to 90 weight % of an alumina component and 20 to 10 weight % of a silica component and the crystal structure of the inorganic long fiber has an intermediate alumina and mullite, the larger the grains of the mullite crystals in its crystal structure, the more it affects the wear resistance of the grinding stone rod. That is, in the inorganic long fiber with large grains, mullite is in progress. As mullite progresses, the inorganic long fiber becomes brittle. Here, when the rod-shaped grinding stone rod using the inorganic long fiber is used to grind the grinding target surface of the workpiece, the front end of the grinding stone rod is pressed on the grinding target surface. In addition, since the rod-shaped grinding stone rod has elasticity that bends in a direction intersecting with the axis, when the front end is pressed on the workpiece, the grinding stone rod bounces or vibrates less on the grinding target surface, and the possibility of the grinding stone rod being damaged or broken is also low. Therefore, when the front end of the grindstone is pressed against the grinding target surface, it is pressed with a large pressing force considering its elasticity to ensure the desired grinding force. Therefore, the front end of the grindstone is easily loaded, and when the inorganic long fibers exposed at the front end are mullitized, the inorganic long fibers become brittle and broken, and are easily worn.

[0016] On the other hand, the inventors have found that when the grindstone rod uses an abrasive in which the inorganic long fibers have 80 to 90 weight % of alumina components and 20 to 10 weight % of silica components, the grinding force of the grindstone rod can be ensured even if the mullite crystal is less than 25 nm. That is, if the inorganic long fibers have an alumina component of more than 80 weight %, the hardness of the grindstone rod can be ensured. In addition, if the mullite crystal is less than 25 nm, mullitization in the inorganic long fibers is suppressed, and thus the embrittlement of the inorganic long fibers is suppressed. Thereby, when the front end of the grindstone rod is pressed on the workpiece to grind the grinding target surface, the embrittlement and crushing of the inorganic long fibers is suppressed, and the inorganic long fibers bite into the workpiece. Furthermore, when the workpiece is ground and polished by the rod-shaped grindstone rod, unlike the case where the side extending along the long side direction is contacted with the grinding target surface as a whole as in the case of a rectangular parallelepiped grindstone to grind the workpiece, the front end can be pressed on the grinding target surface with a pressing force that takes into account the elasticity of the grindstone rod. Therefore, the grindstone rod can have a predetermined grinding force. The present invention is based on these findings.

[0017] In order to solve the above technical problems, the present invention is characterized in that a rod-shaped grindstone rod is pressed at its front end against a grinding target surface of a workpiece to grind the grinding target surface, wherein the grindstone rod has a plurality of inorganic long fibers extending in an axial direction and a resin impregnated in the inorganic long fibers and solidified, a cross section of the inorganic long fibers is exposed at the front end surface, and the grindstone rod has elasticity to bend in a direction intersecting the axial direction, the inorganic long fibers have 80 to 90 weight % of an aluminum oxide component and 20 to 10 weight % of a silicon dioxide component, the average particle size of the mullite crystals is less than 25 nm, a peak of a diffraction line of the (110) plane of mullite appears in a diffraction pattern obtained by irradiating the inorganic long fibers with X-rays, and the average particle size of the mullite crystals is calculated based on the diffraction pattern using the following mathematical formula.

[0018]

Mathematical formula 1

[0019]

[0020] D hkl :The average particle size of (210) plane

[0021] λ: wavelength of X-rays

[0022] θ: glancing angle of X-rays

[0023] β 1 / 2 : The half width of the diffraction line of the (210) plane of mullite with a 2θ of about 26° based on the crystal structure of X-ray diffraction

[0024] In the grinding stone rod of the present invention, in the crystal structure of the inorganic long fiber, the average particle size of the mullite crystal is less than 25nm. Thus, it is possible to suppress the generation of scratches (grinding scars) on the grinding target surface of the workpiece due to the size of the mullite crystal. Therefore, the surface roughness of the grinding target surface can be improved. In addition, in the grinding stone rod of the present invention, in the crystal structure of the inorganic long fiber, the average particle size of the mullite crystal is less than 25nm. Thus, it is possible to suppress the embrittlement of the inorganic long fiber, and therefore, when the front end of the grinding stone rod with the cross section of the inorganic long fiber exposed on the front end face is pressed on the grinding target surface of the workpiece for grinding, the embrittlement and crushing of the inorganic long fiber can be suppressed. Therefore, the wear resistance of the grinding stone rod is improved.

[0025] On the other hand, the inorganic long fibers have an aluminum oxide component of more than 80% by weight, so it is easy to ensure its hardness. In addition, if the mullite crystal is small, the embrittlement of the inorganic long fibers can be suppressed. Therefore, when the front end of the grindstone rod is pressed on the grinding target surface of the workpiece for grinding, the inorganic long fibers can be suppressed from brittle fracture, and the inorganic long fibers bite into the workpiece. Furthermore, when the workpiece is ground and polished by the rod-shaped grindstone rod, unlike the situation where the side extending along the long side direction is contacted with the grinding target surface as a whole as in the case of a rectangular parallelepiped grindstone to grind the workpiece, the front end can be pressed on the grinding target surface for grinding. Moreover, since the rod-shaped grindstone rod has elasticity that bends in a direction intersecting with its axis, even if the front end is pressed on the grinding target surface, the grindstone rod bounces or vibrates on the grinding target surface less, and the possibility of the grindstone rod being damaged or broken is low. Therefore, the desired grinding force can be obtained by pressing the front end of the grindstone rod on the grinding target surface with a pressing force that takes into account the elasticity of the grindstone rod. Therefore, even if the average grain size of the mullite crystals in the grindstone rod is less than 25 nm, the grinding force can be ensured.

[0026] In the present invention, it is preferred that the average particle size of the mullite crystals is less than 20 nm. This can easily improve the surface roughness of the grinding target surface and further improve the wear resistance of the grinding stone rod.

[0027] In the present invention, the alumina content of the inorganic long fibers is preferably 85% by weight or more. In this case, the hardness of the inorganic long fibers can be further increased, and therefore, the grinding force of the grindstone can be easily ensured.

[0028] In the present invention, the resin may be epoxy resin.

[0029] In the present invention, the bending strength can be made above 500 MPa and the bending elastic modulus can be made above 50 GPa. In this case, the pressure of the tip of the grindstone rod pressing on the grinding target surface can be increased, and the desired grinding force can be easily obtained.

[0030] Next, the grinding method of the present invention is characterized in that the grindstone rod is mounted on a vibration tool, and the grindstone rod is vibrated in the axial direction while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece. The grinding method performed while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece includes the grinding method performed while the front end surface of the grindstone rod is pressed against the grinding target surface of the workpiece.

[0031] In addition, the grinding method of the present invention is characterized in that the grindstone rod is mounted on a vibration tool, and the grindstone rod is vibrated in the axial direction and in a direction intersecting the axis of the grindstone rod while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece. The grinding method performed while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece includes the grinding method performed while the front end surface of the grindstone rod is pressed against the grinding target surface of the workpiece.

[0032] Furthermore, the grinding method of the present invention is characterized in that the grindstone rod is mounted on a rotating tool, the front end of the grindstone rod is rotated while being pressed against the grinding target surface of the workpiece, and the cross section of the grindstone rod is circular. The grinding method performed while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece includes the grinding method performed while the front end surface of the grindstone rod is pressed against the grinding target surface of the workpiece. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the front view of the grinding stone.

[0034] Figure 2 is used Figure 1 An explanatory diagram of a method for grinding a workpiece using a grindstone rod.

[0035] Figure 3 is used Figure 1 FIG. 2 is an explanatory diagram of another example of a method for grinding a workpiece using a grindstone rod.

[0036] Figure 4 It is a front view of a cylindrical grinding stone rod.

[0037] Figure 5 is used Figure 4 An explanatory diagram of a method for grinding a workpiece using a grindstone rod.

[0038] Figure 6 is used Figure 4 FIG. 2 is an explanatory diagram of another example of a method for grinding a workpiece using a grindstone rod.

[0039] Figure 7 It is a flow chart of the manufacturing method of the grinding stone rod.

[0040] Figure 8This is a diffraction pattern obtained by irradiating the inorganic long fibers of Example 1 with X-rays.

[0041] Fig. 9 This is a diffraction pattern obtained by irradiating the inorganic long fibers of Comparative Example 1 with X-rays.

[0042] Fig.10 This is a roughness curve of the polishing target surface of the workpiece after being polished by the grindstone rod of Example 1.

[0043] Fig.11 This is a roughness curve of the polishing target surface of the workpiece after being polished by the grindstone rod of Comparative Example 1.

[0044] Fig.12 This is a graph showing the grinding amount of the workpiece after the comparison test.

[0045] Fig.13 This is a graph comparing the wear amounts of the grinding stones after the test.

[0046] Fig.14 This is a diffraction pattern obtained by irradiating the inorganic long fibers of Example 2 with X-rays.

[0047] Fig.15 This is a diffraction pattern obtained by irradiating the inorganic long fibers of the reference example with X-rays.

[0048] Fig.16 This is a diffraction pattern obtained by irradiating the inorganic long fibers of Comparative Example 2 with X-rays.

[0049] Fig.17 This is a roughness curve of the polishing target surface of the workpiece after being polished by the grindstone rod of Example 2.

[0050] Fig.18 This is a roughness curve of the polishing target surface of the workpiece after being polished by the grindstone rod of the reference example.

[0051] Fig.19 This is a roughness curve of the polishing target surface of the workpiece after being polished by the grindstone rod of Comparative Example 2.

[0052] Fig. 20 This is a graph showing the grinding amount of the workpiece after the comparison test.

[0053] Fig.21 This is a graph comparing the wear amounts of the grinding stones after the test. DETAILED DESCRIPTION

[0054] Hereinafter, a grindstone rod according to an embodiment of the present invention will be described with reference to the drawings.

[0055] (grindstone)

[0056] Figure 1It is the front view of the grinding stone. Figure 2 is used Figure 1 An explanatory diagram of a method for grinding a workpiece using a grindstone rod. Figure 3 is used Figure 1 FIG. 2 is an explanatory diagram of another example of a method for grinding a workpiece using a grindstone rod. Figure 4 It is a front view of a cylindrical grinding stone rod. Figure 5 is used Figure 4 An explanatory diagram of a method for grinding a workpiece using a grindstone rod. Figure 6 is used Figure 4 FIG. 2 is an explanatory diagram of another example of a method for grinding a workpiece using a grindstone rod.

[0057] like Figure 1 As shown, the grinding stone rod 10 is in the shape of a rod and has a rectangular cross section. In this example, the grinding stone rod 10 has a rectangular cross section. The grinding stone rod 10 has a plurality of inorganic long fibers 15 extending along the axial direction of its axis L and a resin 16 impregnated in the inorganic long fibers 15 and solidified. The inorganic long fibers 15 are polycrystalline fibers and have an alumina component of 80 to 90% by weight and a silica component of 20 to 10% by weight. The cross section of the inorganic long fibers 15 is exposed at the front end surface 17a of the grinding stone rod 10.

[0058] The grindstone rod 10 has elasticity to bend in a direction intersecting with its axis L. The bending strength of the grindstone rod 10 is above 500 MPa. The bending elastic modulus of the grindstone rod 10 is above 50 GPa. More preferably, the bending strength of the grindstone rod 10 is above 800 MPa, and the bending elastic modulus of the grindstone rod 10 is above 65 GPa. Figure 1 In the drawings, the inorganic long fibers 15 are indicated by dotted lines for convenience, but the inorganic long fibers 15 extend continuously from the front end to the base end of the grinding stone rod 10. In addition, the plurality of inorganic long fibers 15 are sometimes inclined relative to the axis L of the grinding stone rod 10, but the inclination angle in this case is about 10° and does not exceed 20° at most.

[0059] (Grinding method)

[0060] like Figure 2 As shown, the grindstone rod 10 is used by mounting its base end portion on the head of a hand-held vibration tool. The vibration tool is, for example, a pneumatic vibration tool or an ultrasonic vibration tool. The vibration tool reciprocates (vibrates) the grindstone rod 10 mounted on the head in the axial direction. The workpiece W that the grindstone rod 10 grinds is, for example, a mold for resin molding.

[0061] When grinding the workpiece W, the front end portion 17 of the grindstone rod 10 is pressed against the grinding target surface S of the workpiece W from an oblique direction. That is, the grindstone rod 10 is pressed against the grinding target surface S in a posture in which the angle θ between its axis L and the grinding target surface S forms an acute angle. In this example, one long side of the rectangular cross section of the grindstone rod 10 is opposite to the grinding target surface S. In addition, when grinding the workpiece W, the grindstone rod 10 is pressed against the grinding target surface S of the workpiece W from a direction along the axis L with a predetermined pressing force F. Furthermore, the grindstone rod 10 is pressed against the grinding target surface S of the workpiece W from a direction along the axis L with a predetermined pressing force F. Figure 2 As shown by the arrow in , the workpiece W is vibrated in the axial direction when grinding. When the vibration tool 11 is a pneumatic vibration tool, the pneumatic vibration tool vibrates the grindstone rod 10 at a speed of 5000 st / min or more. When the vibration tool 11 is an ultrasonic vibration tool, the ultrasonic vibration tool vibrates the grindstone rod 10 at a frequency of 15 kHz or more.

[0062] In addition, the grinding stone rod 10 is as Figure 3 As shown in FIG. 1 , sometimes the front end face 17a is pressed against the grinding target surface S of the workpiece W from a vertical direction to grind the workpiece W. In this case, the grinding stone rod 10 is also pressed against the grinding target surface S with a pressing force F from the direction along the axis L. Figure 3 As shown by the solid arrow in , the grinding stone rod 10 is vibrated in the axial direction by the vibration tool 11. When the vibration tool 11 is a pneumatic vibration tool, the pneumatic vibration tool vibrates the grinding stone rod 10 at a speed of 5000 st / min or more. When the vibration tool 11 is an ultrasonic vibration tool, the ultrasonic vibration tool vibrates the grinding stone rod 10 at a frequency of 15 kHz or more.

[0063] Here, if Figure 3 As shown by the arrows indicated by the solid lines and the dotted lines, when a pneumatic vibration tool is used, the grinding stone rod 10 may be vibrated by the pneumatic vibration tool in the axial direction and in the direction perpendicular to the axis L. In this case, the pneumatic vibration tool swings the grinding stone rod 10 along an elliptical orbit between strokes for vibrating the grinding stone rod 10 in the axial direction, thereby achieving vibration in the axial direction and in the direction perpendicular to the axis L. In this case, the pneumatic vibration tool vibrates the grinding stone rod 10 at a speed of 5000 st / min or more.

[0064] In addition, when using pneumatic vibration tools, such as Figure 2 As shown, when the front end portion 17 of the grindstone rod 10 is pressed against the grinding target surface S from an oblique direction to grind the workpiece W, the grindstone rod 10 may also vibrate in the axial direction and in a direction perpendicular to the axis L.

[0065] In addition, if Figure 5As shown, the grindstone rod 10 is sometimes used by installing its base end portion on the head of a hand-held rotating tool 11'. In this case, the grindstone rod installed on the rotating tool 11' is preferably as shown in FIG. Figure 4 The cross section of the grinding stone rod 10' is shown as a circle. That is, it is preferred that the cylindrical grinding stone rod 10' is mounted on the rotating tool 11'. The rotating tool 11' is, for example, an electric rotating tool or a pneumatic rotating tool. Figure 5 As shown by the solid arrow in FIG. 1 , the rotating tool 11 ′ rotates the grindstone rod 10 ′ around its axis.

[0066] like Figure 5 As shown, when grinding the workpiece W, the front end portion 17 of the grindstone rod 10' is pressed against the grinding target surface S of the workpiece W from an oblique direction. That is, the grindstone rod 10' is pressed against the grinding target surface S in a posture in which the angle θ between the axis L and the grinding target surface S is an acute angle. In addition, when grinding the workpiece W, the grindstone rod 10' is pressed against the grinding target surface S of the workpiece W from a direction along the axis L with a predetermined pressing force F. Furthermore, the grindstone rod 10' is rotated around the axis in a state in which the front end portion 17 is pressed against the grinding target surface S. The rotating tool 11' rotates the grindstone rod 10 at a rotation speed of 100 rpm or more.

[0067] Here, in the case where the grinding stone rod 10' is mounted on the rotating tool 11' for grinding, as shown in FIG. Figure 6 As shown, the front end surface 17a of the grindstone rod 10' is sometimes pressed against the grinding target surface S of the workpiece W from a vertical direction to rotate. In this case, the grindstone rod 10' is also pressed against the grinding target surface S with a pressing force F from a direction along the axis L. In addition, the rotating tool 11' rotates the grindstone rod 10 at a rotation speed of 100 rpm or more.

[0068] Here, in any of the above-mentioned grinding methods, when the grinding target surface S of the workpiece is ground by the grindstone rod 10, the grindstone rod 10 may bend in a direction intersecting with its axis L due to the pressing force F pressing the grindstone rod 10 against the grinding target surface S or the reaction force from the side of the grinding target surface S.

[0069] The grindstone rods 10 and 10' may be used without being attached to a vibration tool, etc. In this case, the operator presses the tip 17 of the grindstone rods 10 and 10' against the grinding target surface S of the workpiece W to perform manual grinding.

[0070] (Manufacturing method of grinding stone rod)

[0071] Figure 7 It is a flow chart of the manufacturing method of grinding stone rod. Figure 7As shown, the manufacturing method of the grinding stone rod 10 sequentially comprises a spinning step ST1, a calcining step ST2, a sintering step ST3, and a resin impregnation molding step ST4. In the spinning step ST1, an aqueous spinning solution composed of basic aluminum chloride, colloidal silica, and polyvinyl alcohol is dry-spun to obtain a precursor fiber. In the calcining step ST2, the precursor fiber is calcined at a temperature of 900° C. to 1300° C. to form a ceramic to obtain an inorganic long fiber. In the sintering step ST3, the inorganic long fiber is heated at a high temperature of 1300° C. or more for about 20 seconds. The heating temperature in the sintering step ST3 is higher than the heating temperature in the calcining step ST2.

[0072] The resin impregnation molding step ST4 forms bundled yarns by appropriately drawing the inorganic long fibers. In addition, in the resin impregnation molding step ST4, the bundled yarns are impregnated with a thermosetting resin such as an epoxy resin or a phenolic resin. Furthermore, in the resin impregnation molding step ST4, the bundled yarns impregnated with the resin are drawn to form a bundle of bundled yarns. Furthermore, in the resin impregnation molding step ST4, the bundle of bundled yarns impregnated with the resin is pulled out through a mold having an opening of a predetermined shape, and then cured by a heating furnace. Then, the bundle of bundled yarns after the resin is cured is cut to a predetermined length. Thus, a grindstone rod 10 having a predetermined length dimension and a predetermined cross-sectional shape is obtained.

[0073] A specific example of the manufacturing method is shown below. First, in the spinning step ST1, 2.5 kg of partially saponified polyvinyl alcohol with an average degree of polymerization of 1700 is dissolved in 34 kg of an alkaline aluminum chloride aqueous solution containing 13.2% by weight of aluminum ions and 11.45% by weight of chloride ions, and 7.5 kg of colloidal silica containing 20% ​​by weight of silica, to prepare a spinning solution with a viscosity of about 1000 poise / 20°C. Next, the spinning solution is extruded from a spinning nozzle with 1000 holes for dry spinning. In the pre-sintering step ST2, the spun inorganic long fibers are sintered at 900°C to 1300°C to form ceramics to obtain bundled yarns. Then, in the sintering step ST3, the bundled yarns are passed through a tubular furnace at 1300°C to 1400°C and are continuously wound on a first bobbin under tension. At this time, the passing speed of the bundled yarn is adjusted under the condition of a heating time of 20 seconds. Here, the bundled yarn is wound on a plurality of first bobbins.

[0074] In the resin impregnation molding step ST4, bundled yarns are respectively drawn out from the plurality of first bobbins and passed through a resin tank storing uncured resin. In addition, the bundled yarns impregnated with resin passing through the resin tank are aligned and bundled and passed through a heating furnace.

[0075] The resin impregnated in the bundled yarns and the bundles of the bundled yarns may have the following composition.

[0076] Epoxy resin (jER828, manufactured by Mitsubishi Chemical Corporation) 100 parts by weight

[0077] Tetrahydromethylphthalic anhydride (HN2200, manufactured by Hitachi Chemical Co., Ltd.) 85 parts by weight

[0078] Imidazole (2E4MZ-CN, manufactured by Shikoku Chemicals Co., Ltd.) 2 parts by weight

[0079] Here, in the resin impregnation molding process ST4, the bundle of bundled wires impregnated with resin passes through a mold having an opening of a predetermined shape before reaching the heating furnace. Thereby, the cross-sectional shape of the bundle of bundled wires impregnated with resin becomes a shape corresponding to the opening shape of the mold. In addition, in the resin impregnation molding process ST4, the impregnated resin is solidified by passing through the heating furnace. Therefore, the bundle of bundled wires after the resin is solidified is cut into a predetermined size. Thereby, when the opening of the mold is rectangular, a grindstone rod having a predetermined length size and a rectangular cross section can be obtained. When the opening of the mold is circular, a grindstone rod having a predetermined length size and a circular cross section can be obtained.

[0080] (Example 1)

[0081] The grindstone rod 10 of Example 1 is in the shape of a rod, and has a rectangular cross-section perpendicular to the axis L. The grindstone rod 10 has a thickness (dimension in the short side direction of the cross section) of 1 mm, a width (dimension in the long side direction of the cross section) of 4 mm, and a length of 100 mm. The grindstone rod 10 has a bending strength of 1200 MPa and a bending elastic modulus of 115 GPa.

[0082] The grinding stone rod 10 has a plurality of inorganic long fibers 15 extending in the axial direction and a resin 16 impregnated in the inorganic long fibers 15. The inorganic long fibers 15 have an alumina component of 85% by weight and a silica component of 15% by weight. The crystal structure of the inorganic long fibers 15 has mullite crystals and intermediate alumina. The average particle size of the crystal particles of the mullite crystals is 20 nm. The cross section of the inorganic long fibers 15 is exposed at the front end surface 17a of the grinding stone rod 10.

[0083] When the grindstone rod 10 of Example 1 is manufactured, the heating temperature of the calcining step ST2 is 1000° C. The heating temperature of the sintering step ST3 is 1380° C. The heating time in the sintering step ST3 is 20 seconds.

[0084] Here, the crystal structure of the inorganic long fibers 15 is evaluated using X-ray diffraction. That is, after the sintering step ST3 is completed and before the resin impregnation molding step ST4, the inorganic long fibers 15 are irradiated with X-rays to obtain a diffraction pattern. Figure 8This is a diffraction pattern when the inorganic long fibers 15 of Example 1 are irradiated with X-rays. In addition, based on the diffraction pattern, the average particle size of the mullite crystals was calculated by the following general formula.

[0085]

Mathematical formula 1

[0086]

[0087] D hkl :The average particle size of (210) plane

[0088] λ: wavelength of X-rays

[0089] θ: glancing angle of X-rays

[0090] β 1 / 2 : The half width of the diffraction line of the (210) plane of mullite with a 2θ of about 26° based on the crystal structure of X-ray diffraction

[0091] Figure 8 The average particle size of the mullite crystals of the inorganic long fibers 15 obtained from the diffraction pattern shown is Dhkl=20 (nm).

[0092] In addition, as the particle size of the mullite crystal decreases, the peak value of the diffraction line of the (210) surface of mullite decreases, and it is sometimes covered by other diffraction lines. For example, when the particle size of the mullite crystal is less than 25nm, the peak value of the diffraction line of the (210) surface of mullite is sometimes covered by other diffraction lines and the half width of the diffraction line cannot be obtained. In this regard, the inventors conducted experiments and confirmed that the average particle size of the mullite crystal is below 20nm using other measurement methods when the peak value of the diffraction line of the (210) surface of mullite is covered by other diffraction lines and the half width of the diffraction line cannot be obtained. In addition, even if the peak value of the diffraction line of the (210) surface of mullite is covered by other diffraction lines, as long as the peak value of the diffraction line of the (110) surface of mullite appears in the diffraction pattern, it can be judged that the crystal structure of the inorganic long fiber 15 has mullite crystals.

[0093] (Comparative Example)

[0094] The grindstone rod of Comparative Example 1 is in the shape of a rod, and the cross-section shape perpendicular to the axis is a rectangle. The thickness dimension (dimension in the short side direction of the cross section) of the grindstone rod 10 is 1 mm, the width dimension (dimension in the long side direction of the cross section) is 4 mm, and the length dimension is 100 mm. The bending strength of the grindstone rod is 1200 MPa, and the bending elastic modulus is 120 GPa. The grindstone rod of Comparative Example 1 has a plurality of inorganic long fibers extending in the axial direction and a resin impregnated in the inorganic long fibers. The inorganic long fibers have an alumina component of 85% by weight and a silica component of 15% by weight. The crystal structure of the inorganic long fibers has mullite crystals and intermediate alumina. The cross section of the inorganic long fibers is exposed at the front end face of the grindstone rod of Comparative Example 1.

[0095] Fig. 9 This is the diffraction pattern of the inorganic long fiber of Comparative Example 1 when irradiated with X-rays. Fig. 9 In the diffraction pattern shown, the peak of the diffraction line of the (210) plane of mullite clearly appears. Fig. 9 The average particle size of the mullite crystals of the inorganic long fibers of Comparative Example 1 obtained from the diffraction pattern shown is Dhkl=35 (nm). That is, the average particle size of the crystal particles of the mullite crystals is 25 nm or more.

[0096] When manufacturing the grindstone rod of Comparative Example 1, the heating temperature in the calcining step ST2 was 1000° C. The heating temperature in the sintering step ST3 was 1390° C. The heating time in the sintering step ST3 was 30 seconds.

[0097] Compared with the heating temperature of the sintering step ST3 of Example 1, the heating temperature of the sintering step ST3 of Comparative Example 1 is higher. Compared with the heating time of the sintering step ST3 of Example 1, the heating time of the sintering step ST3 of Comparative Example 1 is also longer. As a result, the grinding stone rod of Comparative Example 1 has mullite crystals with an average particle size of 25 nm or more in the crystal structure. Therefore, by controlling the heating temperature and heating time of the sintering step ST3 during the manufacture of the grinding stone rod, the average particle size of the mullite crystals in the crystal structure of the inorganic long fiber can be controlled.

[0098] (Comparative test)

[0099] A comparative test of grinding a workpiece W was conducted using the grindstone rod 10 of Example 1 and the grindstone rod of Comparative Example 1. Fig.10 This is a roughness curve of the grinding target surface of the workpiece after grinding using the grindstone rod of Example 1. Fig.11 This is a roughness curve of the polishing target surface of the workpiece after polishing using the grindstone rod of Comparative Example 1. Fig.12 This is a graph showing the grinding amount of the workpiece after a comparative test of grinding the workpiece using the grindstone rods of Example 1 and Comparative Example 1 was completed. Fig.13This is a graph showing the amount of wear of the grindstone rod after a comparative test of grinding a workpiece using the grindstone rods of Example 1 and Comparative Example 1 was completed.

[0100] In the comparative test, the base end of the grindstone rod 10 was mounted on the head of the hand-held vibration tool 11, and the grinding target surface S of the workpiece W was ground. The vibration tool was a pneumatic vibration tool. The workpiece W to be ground was a mold. The material of the workpiece W was S50C (carbon steel for machine structure).

[0101] More specifically, if Figure 2 As shown, when grinding the workpiece W, the grindstone rod 10 of Example 1 and the grindstone rod of Comparative Example 1 were set to a posture in which the angle θ between the axis L and the grinding target surface S was 30°. In addition, the front end portion 17 of the grindstone rod 10 of Example 1 and the front end portion of the grindstone rod of Comparative Example 1 were pressed against the grinding target surface S with a pressing force F of 6N. Furthermore, the grindstone rod 10 of Example 1 and the grindstone rod of Comparative Example 1 were vibrated at 21000 st / min in the axial direction by the vibration tool 11. Then, the workpiece W was continuously dry-grinded for 3 minutes with respect to the grinding area of ​​30 mm×30 mm.

[0102] from Fig.12 As can be seen from the graph of the grinding amount of the workpiece after the comparative test, the grindstone rod 10 of Example 1 is considered to have the same grinding force as the grindstone rod of Comparative Example 1.

[0103] in addition, Fig.10 The scratch generation in the roughness curve of the grinding target surface of the workpiece after grinding using the grindstone rod 10 of Example 1 is shown. Fig.11 The roughness curve of the grinding target surface of the workpiece after grinding using the grindstone rod of Comparative Example 1 shows that there are few scratches. Furthermore, the surface roughness of the grinding target surface S of the workpiece W when grinding using the grindstone rod 10 of Example 1 is Rz2.0μm. The surface roughness of the grinding target surface S of the workpiece W after grinding using the grindstone rod of Comparative Example 1 is Rz4.1μm. Therefore, when grinding using the grindstone rod 10 of Example 1, the surface roughness of the grinding target surface S of the workpiece W can be improved.

[0104] Furthermore, from Fig.13 As shown in the graph of the wear amount of the grindstone after the comparative test, the wear amount of the grindstone 10 of Example 1 is smaller than that of the grindstone of Comparative Example 1. Therefore, the wear resistance of the grindstone 10 of Example 1 is improved compared with that of the grindstone of Comparative Example 1.

[0105] (Effect)

[0106] In the grinding stone rod 10 of this example, the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm. Thus, it is possible to suppress the generation of scratches (grinding scars) on the grinding target surface of the workpiece due to the size of the mullite crystals. Therefore, the surface roughness of the grinding target surface can be improved.

[0107] In addition, in the grindstone rod 10 of this example, the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm. This can suppress the embrittlement of the inorganic long fibers 15, and thus, when the front end portion 17 of the grindstone rod 10 is pressed against the grinding target surface S of the workpiece W for grinding, the embrittlement and breakage of the inorganic long fibers 15 can be suppressed. Therefore, the wear resistance of the grindstone rod 10 is improved.

[0108] On the other hand, the inorganic long fibers 15 have an aluminum oxide component of more than 80% by weight, so it is easy to ensure its hardness. In addition, if the mullite crystal is small, the embrittlement of the inorganic long fibers 15 can be suppressed. Therefore, when the front end 17 of the grindstone rod 10 is pressed on the grinding target surface S of the workpiece W for grinding, the embrittlement and crushing of the inorganic long fibers 15 can be suppressed, and the inorganic long fibers 15 bite into the workpiece W. In addition, the grindstone rod 10 is different from a rectangular parallelepiped grindstone that grinds by making the entire side surface contact with the grinding target surface of the workpiece W. It grinds by pressing the front end 17 on the grinding target surface of the workpiece W. Moreover, since the grindstone rod 10 has elasticity that bends in a direction intersecting with its axis L, the front end 17 of the grindstone rod 10 can be pressed on the grinding target surface with a pressing force F that takes into account the elasticity of the grindstone rod 10. Therefore, the grindstone rod 10 of Example 1 can ensure grinding force even if the average particle size of the mullite crystal is less than 25nm.

[0109] Here, the inventors have confirmed through experiments that, in the crystal structure of the inorganic long fibers 15 , the smaller the average particle size of the mullite crystals is, the higher the wear resistance of the grindstone rod 10 is.

[0110] In addition, when the inorganic long fibers 15 have an alumina component of 85% by weight or more, the hardness of the inorganic long fibers 15 can be increased compared to the case where the alumina component is less than 85% by weight. Therefore, in order to ensure the grinding force of the grindstone rod 10, it is preferable to have an alumina component of 85% by weight or more. In addition, when the alumina component is 85% by weight or more, the silica component is 15% by weight or less.

[0111] The inorganic long fibers 15 may contain other components in addition to the alumina component and the silica component. In this case, the grinding force of the grindstone rod 10 can be ensured as long as the inorganic long fibers 15 contain 80 to 90 wt % of the alumina component and 20 to 10 wt % of the silica component.

[0112] (Example 2, Reference Example, Comparative Example 2)

[0113] Next, the grinding stone rod 10 of Example 2, Reference Example and Comparative Example 2 is described. The grinding stone rod 10 of Example 2, Reference Example and Comparative Example 2 has a plurality of inorganic long fibers 15 extending in the axial direction and a resin 16 impregnated in the inorganic long fibers 15, similarly to the grinding stone rod 10 of Example 1. The inorganic long fibers 15 have 85% by weight of an alumina component and 15% by weight of a silica component. The crystal structure of the inorganic long fibers 15 has mullite crystals and intermediate alumina. The cross section of the inorganic long fibers 15 is exposed at the front end surface 17a of the grinding stone rod 10 of Example 2 and the reference example.

[0114] The grindstone rods of Example 2, Reference Example, and Comparative Example 2 have the same shape as the grindstone rod 10 of Example 1. That is, the grindstone rods 10 of Example 2, Reference Example, and Comparative Example 2 are rod-shaped, and the cross-sectional shape perpendicular to the axis L is rectangular. The thickness dimension of each grindstone rod 10 is 1 mm, the width dimension is 4 mm, and the length dimension is 100 mm.

[0115] In Example 2, Reference Example and Comparative Example 2, the crystal structure of the inorganic long fibers 15 was evaluated by X-ray diffraction in the same manner as in Example 1. That is, after the sintering step ST3 and before the resin impregnation step ST4, the inorganic long fibers 15 were irradiated with X-rays to obtain a diffraction pattern. Fig.14 This is a diffraction pattern when the inorganic long fibers 15 of Example 2 are irradiated with X-rays. Fig.15 This is a diffraction pattern when the inorganic long fibers 15 of the reference example are irradiated with X-rays. Fig.16 This is a diffraction pattern when the inorganic long fibers 15 of Comparative Example 2 were irradiated with X-rays. As in the case of Example 1, the average particle size of the mullite crystals was calculated based on the diffraction pattern using the general formula.

[0116] from Fig.14 The average particle size of the mullite crystal of the inorganic long fiber 15 obtained by the diffraction pattern of Example 2 shown is Dhkl=10 (nm). That is, the average particle size of the crystal particles of the mullite crystal of the inorganic long fiber 15 in Example 2 is 10nm. Here, the bending strength of the grindstone rod 10 of Example 2 is 1200MPa, and the bending elastic modulus is 112GPa. When manufacturing the grindstone rod 10 of Example 2, the heating temperature of the pre-sintering step ST2 is 1000°C. The heating temperature of the sintering step ST3 is 1370°C. The heating time in the sintering step ST3 is 20 seconds.

[0117] from Fig.15The average particle size of the mullite crystal of the inorganic long fiber 15 obtained by the diffraction pattern of the reference example shown is Dhkl=25 (nm). That is, the average particle size of the crystal particles of the mullite crystal of the inorganic long fiber 15 in the reference example is 25nm. Here, the bending strength of the grindstone rod 10 of the reference example is 1200MPa, and the bending elastic modulus is 116GPa. When manufacturing the grindstone rod 10 of the reference example, the heating temperature of the pre-sintering step ST2 is 1000°C. The heating temperature of the sintering step ST3 is 1385°C. The heating time in the sintering step ST3 is 20 seconds.

[0118] from Fig.16 The average particle size of the mullite crystal of the inorganic long fiber 15 obtained from the diffraction pattern of the comparative example 2 shown is Dhkl=30 (nm). That is, the average particle size of the crystal particles of the mullite crystal of the inorganic long fiber 15 in the comparative example 2 is 30nm. Here, the bending strength of the grindstone rod 10 of the comparative example 2 is 1200MPa, and the bending elastic modulus is 117GPa. When manufacturing the grindstone rod 10 of the comparative example 2, the heating temperature of the calcining step ST2 is 1000°C. The heating temperature of the sintering step ST3 is 1390°C. The heating time in the sintering step ST3 is 20 seconds.

[0119] (Comparative test)

[0120] Using the grindstone rod 10 of Example 2, the grindstone rod 10 of the reference example, and the grindstone rod 10 of Comparative Example 2, a comparative test similar to the above-mentioned comparative test was performed. Fig.17 This is a roughness curve of the grinding target surface of the workpiece after grinding using the grindstone rod 10 of Example 2. Fig.18 1 is a roughness curve of the grinding target surface of the workpiece after grinding using the grindstone rod 10 of the reference example. Fig.19 : is a roughness curve of the grinding target surface of the workpiece after grinding using the grinding stone rod 10 of Comparative Example 2. Fig.17 , Fig.18 , Fig.19 In the figure, the horizontal axis is the measured length (mm) and the vertical axis is the height (μm).

[0121] Fig. 20 Graph showing the grinding amount of a workpiece after a comparative test of grinding a workpiece using the grindstone rod 10 of Example 2, the grindstone rod 10 of the reference example, and the grindstone rod 10 of the comparative example. Fig. 20 In the Fig.12 The grinding amount of the grindstone rod 10 of Example 1 and the grinding amount of the grindstone rod 10 of Comparative Example 1 are shown. Fig.21 Graph showing the wear amount of the grindstone rod 10 after a comparative test of grinding a workpiece using the grindstone rod 10 of Example 2, the grindstone rod 10 of the reference example, and the grindstone rod 10 of the comparative example. Fig.21 In the Fig.13 The wear amount of the grindstone rod 10 of Example 1 and the wear amount of the grindstone rod 10 of Comparative Example 1 are shown.

[0122] from Fig. 20 As shown in the graph of the workpiece grinding amount after the comparative test, the grindstone rod 10 of Example 1 (Dhkl = 20 (nm)), the grindstone rod 10 of Example 2 (Dhkl = 10 (nm)), and the grindstone rod 10 of the reference example (Dhkl = 25 (nm)) all have the same grinding force as the grindstone rod 10 of Comparative Example 1 (Dhkl = 35 (nm)) and the grindstone rod 10 of Comparative Example 2 (Dhkl = 30 (nm)). Specifically, the grinding amount of the grindstone rod 10 of Example 1 is 0.110 g. The grinding amount of the grindstone rod 10 of Example 2 is 0.109 g. The grinding amount of the grindstone rod 10 of the reference example is 0.111 g. The grinding amount of the grindstone rod 10 of Comparative Example 2 is 0.111 g. The grinding amount of the grindstone rod 10 of Comparative Example 2 is 0.111 g.

[0123] In addition, from Fig.21 As shown in the graph of the wear amount of the grindstone rod 10 after the comparative test, the wear amount of the grindstone rod 10 of Example 1 (Dhkl = 20 (nm)), the wear amount of the grindstone rod 10 of Example 2 (Dhkl = 10 (nm)), and the wear amount of the grindstone rod 10 of the reference example (Dhkl = 25 (nm)) are less than the wear amount of the grindstone rod 10 of Comparative Example 1 (Dhkl = 35 (nm)) and the wear amount of the grindstone rod 10 of Comparative Example 2 (Dhkl = 30 (nm)). Specifically, the wear amount of the grindstone rod 10 of Example 1 is 0.0029 g. The wear amount of the grindstone rod 10 of Example 2 is 0.0028 g. The wear amount of the grindstone rod 10 of the reference example is 0.0029 g. The wear amount of the grindstone rod 10 of Comparative Example 1 is 0.0046 g. The wear amount of the grindstone rod 10 of Comparative Example 2 is 0.0031 g. The wear amount of the grindstone rod 10 of Example 1, Example 2 and Reference Example is less than 0.003 g, which is 35% or more lower than that of the grindstone rod of Comparative Example 1.

[0124] In addition, through experiments conducted by the inventors, it was confirmed that, in the crystal structure of the inorganic long fibers 15 of the grindstone rod 10, the smaller the average particle size of the mullite crystals, the smaller the wear amount of the grindstone rod 10. That is, when the particle size of the mullite crystals is less than 10 nm and the peak of the diffraction line of the (210) plane of the mullite is buried by other diffraction lines and the correct particle size cannot be obtained, the wear amount of the grindstone rod 10 is lower than the wear amount of the grindstone rod 10 of Example 2. Therefore, the smaller the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15, the higher the wear resistance of the grindstone rod 10.

[0125] Next, according to the roughness curve ( Fig.17 ) calculated that the surface roughness of the grinding target surface S of the workpiece W is Rz2.04μm. In addition, according to the roughness curve ( Fig.18 ) calculated that the surface roughness of the grinding target surface S of the workpiece W is Rz2.06μm. According to the roughness curve ( Fig.10 ) calculated that the surface roughness of the polishing target surface S of the workpiece W was Rz2.05 μm. This value is between the surface roughness value of the workpiece polished by the grindstone rod 10 of Example 2 and the surface roughness value of the workpiece polished by the grindstone rod 10 of the reference example.

[0126] In addition, according to the roughness curve ( Fig.17 ) calculated that the surface roughness of the grinding target surface S of the workpiece W is Rz2.17μm. Furthermore, according to the roughness curve ( Fig.11 ) calculated that the surface roughness of the grinding target surface S of the workpiece W is Rz4.13μm. Therefore, the smaller the average particle size of the crystal particles of the mullite crystal of the inorganic long fiber 15, the more it can suppress the generation of scratches, etc., and the smaller the surface roughness of the grinding target surface S of the workpiece W will be.

[0127] (Effect)

[0128] As confirmed by the above comparative test, in the grindstone rod 10, even if the average grain size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm, the same grinding force as when the average grain size of the mullite crystals is 25 nm or more can be obtained.

[0129] Furthermore, if the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 of the grindstone rod 10 is reduced, the generation of scratches and the like is suppressed, and the surface roughness of the grinding target surface S of the grind workpiece W after grinding is reduced. Therefore, if the grindstone rod 10 in which the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm is used, the surface roughness of the grinding target surface S of the grind workpiece W after grinding can be reduced compared to the case where the average particle size of the mullite crystals is 25 nm or more.

[0130] Furthermore, the wear resistance of the grindstone rod 10 is improved when the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm, compared with the case where the average particle size of the mullite crystals is 25 nm or more.

[0131] In addition, if the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is 20 nm or less, the surface roughness of the grinding target surface S of the grinded workpiece W can be reduced compared to the case where the average particle size of the mullite crystals exceeds 20 nm. In addition, if the average particle size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is 20 nm or less, the wear resistance of the grindstone rod 10 is further improved compared to the case where the average particle size of the mullite crystals exceeds 20 nm.

Claims

1. A grindstone rod, which is a rod-shaped grindstone rod whose front end is pressed against a grinding target surface of a workpiece to grind the grinding target surface, wherein: The grinding stone rod has a plurality of inorganic long fibers extending in an axial direction and a resin impregnated in the inorganic long fibers and solidified, a cross section of the inorganic long fibers is exposed at a front end surface, and the grinding stone rod has elasticity to bend in a direction intersecting the axial direction. The inorganic long fibers have 80 to 90 weight percent of an aluminum oxide component and 20 to 10 weight percent of a silicon dioxide component. The inorganic long fiber has a crystal structure of mullite crystals and intermediate alumina. The average particle size of the mullite crystals is less than 25 nm. In the diffraction pattern obtained by irradiating the inorganic long fibers with X-rays, a peak of a diffraction line of the (110) plane of mullite appears. The average particle size of the mullite crystals is calculated based on the diffraction pattern using the following mathematical formula: 【Mathematical formula 1】 D hkl : Average particle size of (210) plane, λ: wavelength of X-rays, θ: glancing angle of X-rays, β 1 / 2 : The half width of the diffraction line of the (210) plane of mullite, where 2θ of the crystal structure based on X-ray diffraction appears around 26°.

2. The grinding stone rod according to claim 1, characterized in that The average particle size of the mullite crystals is below 20 nm.

3. The grinding stone rod according to claim 1, characterized in that: The inorganic long fibers have an alumina content of more than 85% by weight.

4. The grinding stone rod according to claim 1, characterized in that The resin is an epoxy resin.

5. The grinding stone rod according to claim 1, characterized in that The bending strength is above 500MPa and the bending elastic modulus is above 50GPa.

6. A grinding method, characterized in that: The grindstone rod according to claim 1 is mounted on a vibration tool, and the grindstone rod is vibrated in the axial direction while the front end portion of the grindstone rod is pressed against the grinding target surface of the workpiece.

7. A grinding method, characterized in that: The grindstone rod according to claim 1 is mounted on a vibration tool, and the grindstone rod is vibrated in the axial direction and in a direction intersecting the axis of the grindstone rod while the front end of the grindstone rod is pressed against the grinding target surface of the workpiece.

8. A grinding method, characterized in that: The grindstone rod according to claim 1 is mounted on a rotating tool, and the front end of the grindstone rod is rotated in a state where it is pressed against a grinding target surface of a workpiece. The cross section of the grinding stone rod is circular.

Citation Information

Patent Citations

  • Alumina fiber and alumina fiber aggregate

    CN105051272A

  • Polishing brush and polishing method

    CN105324214A

  • Super abrasive grain vitrified bond grinding stone and manufacture thereof

    JP1989271177A

  • Ceramic fiber for processed material, its production and processed material containing the same

    JP1998183427A

  • Grinding wheel

    JP2005297139A